أحكام الحضانة في الفقه الإسلامي وقانون الأحوال الشخصية الليبي - Isniba, Abdallah Elsharif Ahmed; Ezbeyda, Hamed Abdelsalam Mansour (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: There are childcare problems from the perspective of Sharia and the Personal Status Law. This research deals with the provisions of custody in Islamic jurisprudence compared to the Libyan Personal Status Law. The research is a normative jurisprudential and inductive approach by Comparative analysis through the study of the provisions of Islamic Sharia related to the subject of research and compared with the provisions of the Libyan Personal Status Law. The study reached several results that the Libyan Personal Status Law